2023 Southeast Research and Extension Center Agricultural Research Report - J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2023)
The 2023 Southeast Research and Extension Center Agricultural Research report includes research conducted in the areas of beef cattle management, cropping systems, and forage crops. Topics include various grazing and nutrient input for steers and heifers; wheat, soybean, and corn production practices and results, as well as soil health practices; and burning and nutrient practices along with efforts for improvement of native and tall fescue range grasses.
Keywords: variety selection; chemical control; wheat; cropping systems; beef; cattle management; planting date; biomass; forages; weaning; southeast Kansas; grazing; fescue; steers; heifers; corn; weather